Does Social Health Insurance Close the Gap: The Case of Socioeconomic Status and Preterm Low-Birth-Weight Survival. (July 2015) - Hsieh, Vivian Chia-Rong; Shieh, Shwn-Huey; Chen, Chiu-Ying; Liou, Saou-Hsing; Hsiao, Yu-Chen; Wu, Trong-Neng
Using a retrospective cohort study design, we report empirical evidence on the effect of parental socioeconomic status, primary care, and health care expenditure associated with preterm or low-birth-weight (PLBW) babies on their mortality (neonatal, postneonatal, and under-5 mortality) under a universal health care system. A total of 4668 singleton PLBW babies born in Taiwan between January 1 and December 31, 2001, are extracted from a population-based medical claims database for a follow-up of up to 5 years. Multivariate survival models suggest the positive effect of higher parental income is significant in neonatal period but diminishes in later stages. Consistent inverse relationship is observed between adequate antenatal care and the three outcomes: neonatal hazard ratio (HR) = 0.494, 95% confidence interval (CI) = 0.312 to 0.783; postneonatal HR = 0.282, 95% CI = 0.102 to 0.774; and under-5 HR = 0.575, 95% CI = 0.386 to 0.857. Primary care services uptake should be actively promoted, particularly in lower income groups, to prevent premature PLBW mortality.